Critical events and pivotal factors as tools for analyzing the sustainability of online study programs - Suhonen Jarkko; Sutinen Erkki (SPRINGER, 2022)
A critical aspect of designing and running online study programs is the identification of factors and elements that could potentially threaten the continuation of studies. In this study, we first identified a set of critical events that occurred in the running of a Finnish online doctoral study program over 16 years. Next, we analyzed the events using a four-pillar sustainability model, which consisted of the economic, social, environmental, and ethical pillars. We detected several contextually relevant and dynamic pivotal factors related to each of the pillars, which had effects on the sustainability of the program at the time of the critical events. The analysis revealed that positive pivotal factors in one sustainability pillar can be used to compensate for negative pivotal factors in the other pillars. Two aspects that were crucial for the sustainability of the online doctoral study program were the resilience and shared commitment of the community involved in its activities, which helped in overcoming any challenges encountered. Based on this study, we recommended that future research should design novel solutions that help online study programs to proactively identify potential critical events and related pivotal factors. Furthermore, studies should find creative approaches for constructively coping with critical events that have been identified.